Extended Reality and Metaverse Immersive Technology in Times of Crisis - Jung, Timothy; tom Dieck, M. Claudia; Correia Loureiro, Sandra Maria (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book features the latest research in the area of immersive technologies as presented at the 7th International Extended Reality (XR) Conference, held in Lisbon, Portugal in 2022. Bridging the gap between academia and industry, it showcases the latest advances in augmented reality (AR), virtual reality (VR), extended reality (XR) and metaverse and their applications in various sectors such as business, marketing, retail, education, healthcare, tourism, events, fashion, entertainment, and gaming. The volume gathers selected research papers by prominent AR, VR, XR and metaverse scholars from around the world. Presenting the most significant topics and latest findings in the fields of augmented reality, virtual reality, extended reality and metaverse, it will be a valuable asset for academics and practitioners alike.
" Opening and Closing Virtual Reality" The Effects of Openness on Interpretation of and Attitude towards Virtual Reality Advertisements -- AR In-Store Solutions for Different Fashion Retail Environments: Retailers' Perspectives -- How Cognitive Flexibility Affects Sense of Power in a Coffee Virtual Setting: the Moderating Role of Personality Traits -- The Great Unknown: How Brand Familiarity Affects the Relationship Between Augmented Reality and Brand Attitude in the Retail Industry -- Augmented Reality (AR) Brand Storytelling: The Role of Flow in Attitude Formation and Associative Learning.
Keywords: Business information services; Social sciences -- Data processing; Multimedia systems; Digital humanities; IT in Business; Business Information Systems; Computer Application in Social and Behavioral Sciences; Multimedia Information Systems; Digital Humanities